Compostos voláteis e parâmetros de qualidade de diferentes genótipos de frutos de Butia odorata - Ferrão, Tassiane dos Santos (2012)
The Butia odorata has received special attention from the scientific community because of their nutritional and functional properties that have been revealed, in addition to its rightdown sensory characteristics. The aim of this study was to characterize different genotypes from Butia odorata fruit collected in Santa Maria - RS (SM) and Santa Rosa - RS (SR) regions during three consecutive harvests in relation to various physical and chemical properties. Many analyses were performed like: biometric, color and quality parameters, fatty acid composition in the Butia pulp. An HS-SPME method was developed for the isolation and subsequent quantification (GC-FID) and identification (GC/MS) of volatile compounds (VCs). The biometric parameters results showed pulp yields between 40.38 and 73.91%. The color of the pulp ranged between yellow and orange shades. TSS ranged between 12.39 and 15.50 °Brix, acidity between 0.69 and 2.26 g% citric acid and pH between 3.17 and 3.95. The fruit had humidity between 78.04 and 85.85 g%; ashes between 0.47 and 0.77 g%; protein between 0.57 and 0.93 g%, crude fiber between 0.84 and 4.02 g%; lipid between 0.12 and 2.27 g%. The fatty acids such as palmitic acid, linoleic and linolenic acids were found in abundance. It was possible to observe the partial discrimination between the two regions in the PCA using the physico-chemical variables. The samples from SR characterized by high scores for lipids and palmitic acid, while SM samples showed a higher humidity and TSS. The method employed use DVB/CAR/PDMS fiber for the VCs extraction of the centrifuged Butia pulp , added with 30% NaCl, and maintaining the system at a temperature of 35 °C for 45 minutes, under stirring. The volatile fraction was analyzed in GC and were identified 77 compounds among acids (5), alcohols (14), aldehydes (9), ketones (12), lactones (3), terpenes (2) and esters (34). The ethyl hexanoate compound was the major compound in almost samples. The PCA from VCs enabled to realize grouping of samples into two groups according to region of origin. The fruits from Santa Maria showed a high content of esters and the fruits from Santa Rosa had higher concentrations of alcohols and aldehydes. An exploratory analysis of the variables of physico-chemical composition and volatile of the samples was observed using PCA. In the graphs analysis also realized a partial separation of samples according to their region: the samples SM2-10 and RS1-11 distanced themselves from the other and it indicates greater particularity in their chemical compositions. Therefore the fruits (Butia odorata) showed great variability in biometric characteristics, physico-chemical and volatile profiles according to region of origin. It indicates a strong influence of soil and climatic factors. In this study, the nutritional characteristics and high yield pulp of some Butia fruits demonstrated the high potential for fresh consumption or for the manufacture of processed products